2014
DOI: 10.1111/itor.12132
|View full text |Cite
|
Sign up to set email alerts
|

Economic selection of process mean and lot‐sizing decisions for multi‐newsvendor supply chain

Abstract: Two related problems are integrated in this paper, the first is the targeting problem and another is production/inventory decisions in a supply chain. The supply chain under consideration consists of a supplier of raw material, a single producer, and multiple newsvendors. The producer can adjust the process mean before starting the production run. Once set to a certain target value, the process mean is not changed until the production lot is completed. At the end of a production run, the producer screens the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…They concluded that demand variation should not be neglected in the integrated inventory-targeting problem. Darwish and Aldaihani 15 studied the integrated inventory-targeting problem for a single-vendor multi-newsvendor supply chain. They demonstrated the importance of integration through a illustrative examples.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They concluded that demand variation should not be neglected in the integrated inventory-targeting problem. Darwish and Aldaihani 15 studied the integrated inventory-targeting problem for a single-vendor multi-newsvendor supply chain. They demonstrated the importance of integration through a illustrative examples.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Supply chains (SCs) have been defined in many literature studies, they cover all the activities engaged in production from the raw material till the disposal at the destined customer with many partners involved to perform such activities (Pratima and Sharma, 2014;Shah, 2009;Darwish and Aldaihani, 2015;Dalalah, 2016). In particular, the SC encompasses the footsteps necessary to carry a good or service from the supplier or manufacturer to the client.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous replenishment policies with fixed disposal costs were also addressed by Pince et al (2008). Rate-based continuous replenishments policies with deterministic demand have been addressed in Darwish and Aldaihani (2015). This paper introduces a variant of the JRP with LSP and demand constraints.…”
Section: Introductionmentioning
confidence: 99%